Oily Wastewater Treatment: Methods, Challenges, and Trends - Medeiros, Alexandre D’Lamare Maia de; Silva Junior, Cláudio José Galdino da; Amorim, Julia Didier Pedrosa de; Durval, Italo José Batista; Costa, Andréa Fernanda de Santana; Sarubbo, Leonie Asfora (Processes, 2022)
The growing interest in innovations regarding the treatment of oily wastewater stems from the fact that the oil industry is the largest polluter of the environment. The harm caused by this industry is seen in all countries. Companies that produce such wastewater are responsible for its treatment prior to disposal or recycling into their production processes. As oil emulsions are difficult to manage and require different types of treatment or even combined methods, a range of environmental technologies have been proposed for oil-contaminated effluents, such as gravity separation, flotation, flocculation, biological treatment, advanced oxidation processes, and membranes. Natural materials, such as biopolymers, constitute a novel, sustainable solution with considerable potential for oily effluent separation. The present review offers an overview of the treatment of oily wastewater, describing current trends and the latest applications. This review also points to further research needs and major concerns, especially with regards to sustainability, and discusses potential biotechnological applications.